AN OVERVIEW IN HISTORY FOR RESILIENCE TO COVID-19 - Macías-Valadez Treviño, María Elena; Gama Campillo, Lilia María; Zurita Macías-Valadez, Marcela; Rodríguez Quevedo, Fernando (Kuxulkab', 2020)
An overview of pandemics which have affected, in different time and places, the health of thousands of people is presented. All of them have brought to the population problems with a strong sociocultural, economic, political, and religious impact. Pandemics, the global spread of an infectious disease, have occurred throughout history, reaching thousands of people regardless age, sex, or social status. Pandemics have wreaked havoc on public health at high cost but have also left lessons for the need to recover and innovate to resolve the crisis and move on; in other words, to be resilient.
Keywords: Pandemics; Historical overview; Resilience